Edgedancer / Brandon Sanderson. - Sanderson, Brandon (Gollancz, 2024)
Three years ago, Lift asked a goddess to stop her from growing older - a wish she believed was granted. Now, in 'Edgedancer', the barely teenage nascent Knight Radiant finds that time stands still for no one. Although the young Azish emperor granted her safe haven from an executioner she knows only as Darkness, court life is suffocating the free-spirited Lift, who can't help heading to Yeddaw when she hears the relentless Darkness is there hunting people like her with budding powers. The downtrodden in Yeddaw have no champion, and Lift knows she must seize this awesome responsibility.